The 2021 Activity of the Fast-radio-burst-emitting Galactic Magnetar SGR 1935+2154 as Observed by NASA’s Fermi Gamma-Ray Burst Monitor - Noor ul Sabah Rehan; Alaa I. Ibrahim (The Astrophysical Journal, 2023)
The galactic, fast-radio-burst-emitting magnetar SGR 1935+2154 entered an active X-ray burst episode in 2021 September, nearly a year after emitting a fast radio burst with an X-ray counterpart. We report on the temporal and spectral properties of the activity, which included bright intermediate flares, and present a burst catalog of the Fermi Gamma-Ray Burst Monitor observations. We compare this activity to the previous 6 yr history of the source since its discovery in 2014. The bursts show a mean log-Gaussian duration T _100 ∼ 77.34 ms, a cutoff power-law peak energy E _peak ∼ 26.62 keV, and a photon index Γ _CPL ∼ 0.49, and blackbody soft and hard temperatures kT _BBs ∼ 5.23 keV and kT _BBh ∼ 9.24 keV, respectively. The burst fluence spans 3 orders of magnitude (10 ^−8 –10 ^−5 erg cm ^−2 ) and follows ${dN}/{dS}\propto {S}^{-0.93}$ . The anticorrelation between the blackbody temperature and the emission area is weaker in the hard component at ${R}_{BBh}^{2}\propto {{kT}}_{BBh}^{-4.56}$ but is improved in the soft component at ${R}_{BBs}^{2}\propto {{kT}}_{BBs}^{-1.63}$ , compared to previous activities, with an overall ${R}_{BB}^{2}\propto {{kT}}_{BB}^{-3.82}$ correlation. The 2021 bursts have higher average and integrated fluence than the 2014–2020 episodes and are relatively shorter than the 2019–2020 activities yet comparable to the earlier episodes. During 2014–2021, the burst mean peak energy ( E _peak ) shows a slight softening and is generally softer than other magnetars. We discuss our results in terms of magnetar physics and emission mechanisms.